Evaluation of the vascular calcifications and bone mineral disorder of the erc in hemodialysis: Evaluación de las calcificaciones vasculares y trastorno mineral óseo de la ERC en hemodiálisis - Castillo Velarde, Edwin (2018)
ABSTRACT Introduction: Vascular calcifications are part of the systemic disorders of bone mineral metabolism in chronic kidney disease (CKD) and represent one of the main causes of mortality.  Objective: To determine the clinical characteristics, prevalence of vascular calcifications and biochemical alterations of the bone mineral disorder in patients with CKD in hemodialysis therapy. Methods: Analytical, cross-sectional and non-experimental study. The prevalence of vascular calcifications (abdominal aorta) was determined according to the validated score (Kaupilla). The association of qualitative variables was used the Pearson Chi-Square. Results: The population included (n: 49), 65% of the patients were incidents in hemodialysis (> 6 months) with a mean hemodialysis time of 2.8 years. The not incident or new patients on hemodialysis (<6 months) was 35%. The average age was 62.1 years, 53% female and 47% male. 67% reached some degree of vascular calcification (Kaupilla score greater than 1) and 45% presented a score higher than 3 (score associated with cardiovascular risk) and that was predominant in the incident population on hemodialysis. 55% had at least one of the biochemical alterations of bone mineral disease (hypercalcemia, hyperphosphatemia or hyperparathyroidism). The association between the biochemical alterations of the bone mineral disorder and the vascular calcification index was not found in this study. Conclusion: Most patients on hemodialysis present some degree of vascular calcification, so it is important to recognize and prevent vascular calcifications because of the cardiovascular risk that it has. Key words: Vascular calcifications; Kaupilla score; Chronic kidney disease. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1590